Evaluation of the Impact of Intratumoral Heterogeneity of Esophageal Cancer on Pathological Diagnosis and P16 Methylation and the Representativity of Endoscopic Biopsy - Qin, Yu; Zhou, Jing; Fan, Zhiyuan; Gu, Jianhua; Li, Xinqing; Lin, Dongmei; Deng, Dajun; Wei, Wenqiang (Frontiers in Oncology, 2021)
Background: P16 methylation is expected to be potential diagnostic and therapeutic targets for esophageal cancer (EC). Intratumoral heterogeneity (ITH) of EC has been mentioned, not been quantitative measured yet. We aimed to clarify the impact of ITH on pathological diagnosis and P16 methylation, and concordance between endoscopic biopsy and corresponding surgically resected tissue. Methods: We designed a systematic sampling method (SSM) compared with general sampling method (GSM) to obtain EC tumor tissue, tumor biopsy and normal squamous epithelium biopsy. MethyLight assay was utilized to test P16 methylation. All specimens obtained by SSM were pathological diagnosed. Results: 81 cases were collected by GSM, 91.4% and 8.6% of them were esophageal squamous cell carcinomas (ESCCs) and esophageal adenocarcinomas (EADs). 9 SSM cases were 100.0% ESCC. The positive rates of P16 methylation of GSM tumor and normal tissues were 63.0% (51/81) and 32.1% (26/81). For SSM samples, tumor tissues were 100.0% (40/40) EC and 85.0% (34/40) P16 methylated; tumor biopsy were 64.4% (29/45) diagnosed of EC and 68.9% P16 methylated; corresponding normal biopsy were 15.7% (8/51) dysplasia and 54.9% (28/51) P16 methylated respectively. The concordance of pathological diagnosis and P16 methylation between tumor biopsy and corresponding tumor tissue was 75.0% and 62.5%. Conclusion: The SSM we designed was efficient in measuring the ITH of EC. We found inadequate concordance between tumor biopsy and tissue in pathological diagnosis and P16 methylation. Keywords: Esophageal cancer, P16 methylation, intratumoral heterogeneity, endoscopic biopsy, representativity.